PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PARUNG - Nabila Aliya Zahra; Ratna Sari (Journal of Research and Publication Innovation, 2025)
This research aims to find out the influence of the work environment and work discipline on the performance of employees at the Parung District Office, both partially and simultaneously. The method used is a quantitative method with multiple linear regression analysis techniques. The t test results show that the work environment has a significant effect on employee performance with a calculated t value of 11.008 and a significance of 0.000. The F test shows that the work environment and work discipline simultaneously have a significant effect on employee performance with a calculated F value of 63,648, greater than the table F of 3.19 and a significance of 0.000. The value of the coefficient of determination (R Square) of 0.850 shows that the relationship between variables is very strong. Thus, it can be concluded that the work environment and work discipline have a significant and strong influence on the performance of employees at the Parung District Office.